Efektivitas β-Karoten pada Nauplius Artemia - Ernawati; Saddang Saddang; Irwan Irwan (Jurnal Airaha, 2020)
The research aimed at knowing the effectiveness carotenoids in the body of nauplius artemia of β-carotene enriched. This research used a completely randomized design with 4 treatment dosage (0, 5, 10, 15 ppm) and each three replications. The study was conducted for 20 days using a maintenance container in the form of a plastic basin with capacity of 3 L. β-carotene enrichment was carried out for 8 hours/day by adding β-carotene to the maintenance medium. Anova result show thet the best best β-carotene enrichment at 08.00-16.00 WITA and 23.00-07.00 WITA is best obtained at a dosage of 10 ppm, which isi 8,812 ppm and 10,028 ppm and the best time to absorb is enrichment at night. During the study experiment, water quality parameters showed the optimal range, salinity 30,0-33,0, temperatures ranging from 27,0-30,2oC, pH 7,8-8,0 and DO 4,5-5,6 ppm.